2008
DOI: 10.1007/s11695-008-9671-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Roux-en-Y Gastric Bypass and Its Early Effect on Blood Pressure

Abstract: LRYGB is associated with an early reduction in BP and antihypertensive medication usage which is maintained at 1 year after surgery. This early impact on blood pressure occurs before any significant weight loss is achieved thereby suggesting a hormonal mechanism that may be involved for the changes observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 27 publications
5
58
0
1
Order By: Relevance
“…Table 1 shows the basic characteristics of these 9 studies. These included one randomized controlled trial, one control clinical trial, one retrospective study, and six prospective studies [17][18][19][20][21][22][23][24][25]. The nine studies involved a total of 2756 patients (3 studies were from Sweden, 2 from United States of America, and one each from United Kingdom, Norway, China, and Denmark).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shows the basic characteristics of these 9 studies. These included one randomized controlled trial, one control clinical trial, one retrospective study, and six prospective studies [17][18][19][20][21][22][23][24][25]. The nine studies involved a total of 2756 patients (3 studies were from Sweden, 2 from United States of America, and one each from United Kingdom, Norway, China, and Denmark).…”
Section: Resultsmentioning
confidence: 99%
“…Ahmed et al [20], showed that hypertension remission rate was 66% in a Prospective study on 100 patients, suggesting a hormonal mechanism maybe involved for the changes observed, various neuroendocrine changes have been postulated to play a role in this. The gut peptide glucagon-like peptide 1 (GLP-1) has been implicated by some in the early improvement in glycemic control after LRYGBP [26].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The benefits of bariatric surgery, with improvement in parameters of the metabolic syndrome, have been long the object of study by several authors (1,2,6,12,42) . Few studies have aimed to observe the differences between genders and age groups after bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in blood pressure can be seen as early as 1 week postoperative [118]. Antihypertensive medications should be adjusted and patients' blood pressure should be monitored periodically.…”
Section: Medical Management Of Comorbidities and Medication Adjustmentmentioning
confidence: 99%